Representasi Nilai Bushido Tokoh Katakuri Pada Anime One Piece - Girsang, Gleysias Reyznanda (KIRYOKU, 2025)
This research is entitled “Representation of Bushido Value of Katakuri Character in One Piece Anime”. The purpose of this study is to describe the representation of bushido values reflected in the attitude of Katakuri's character and the attitude of other characters towards the bushido value of Katakuri's character in the One Piece anime (1999). The research method used is qualitative method. Data analysis was conducted based on Wellek & Warren's theory of literary sociology and Saussure's theory of semiotics. The results showed that there are four types of bushido values in total (9) data, namely (1) Gi value data, (2) Jin value data, (4) Rei value data, and (2) Meiyou value data. There are two types of attitudes of other characters towards the bushido value of Katakuri, namely (2) positive attitude data and (3) negative attitude data. The bushido value upheld by Katakuri shows a strong character like a Japanese knight.